Model Pemberdayaan UMKM melalui Zakat Produktif: Studi Kasus Implementasi Program Z-Mart dan Z-Chicken BAZNAS Kabupaten Jember: Program Bantuan Modal usaha Z-Mart dan Z-Chicken BAZNAS Kabupaten Jember - Zahriyah, Aminatus; Maulina Arianta, Citra Oriza; Kamila, Faisya Saffa; Dari, Shinta Wulan (LSM Catimore dan Sahabat, 2025)
The MSME empowerment program through productive zakat is one of the crucial steps in improving the economic welfare of the community, especially for less fortunate MSME actors. This study focuses on the implementation of the Z-Mart and Z-Chicken programs initiated by BAZNAS Jember Regency as a model of MSME empowerment through productive zakat. The main objective of this program is to provide business capital, training, and mentoring to MSME actors so that they can develop their businesses further. This community service aims to analyze the implementation of the Z-Mart and Z-Chicken programs in empowering MSMEs in Jember Regency, as well as to identify factors that influence the success of the program. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation from MSME actors who participated in the Z-Mart and Z-Chicken programs, as well as other related parties. The results of the study show that the Z-Mart and Z-Chicken programs have had a positive impact on MSME empowerment in Jember Regency. This program has succeeded in increasing the income, turnover, and business scale of MSME actors. In addition, this initiative also improves the managerial and entrepreneurial capabilities of MSME actors, showing that productive zakat can be an effective tool in supporting community economic growth.